On Mathematical Approach to Economic Problems - Jurek, Witold (Studia Oeconomica Posnaniensia, 2013)
The paper is divided into three parts devoted to the following: the place of economics among the sciences; the views of selected Polish economists on the formalization (mathematization) of economics; and the formal (mathematical) scientific procedures used in economics today along with departures from these procedure and the potential consequences of such departures. After the first two parts of the paper, characterized as reviews, the third presents a very general scheme of the mathematical approach to economic problems as well as departures from this scheme. The problems of departures can be divided into two groups: the first being the mathematization of problems that do not need such an approach, the passive assumption of schemes appropriate for other sciences, the passive usage of various algorithms and the various computer programs used. Secondly, the paper discusses the potential consequences of such departures on the results of scientific research.